A Relevance of Learning a Foreign Language for an Early Age | Relevansi Pembelajaran Bahasa Asing untuk Anak Usia Dini - Aim Matun Nihayati Al Muchith; Nely Rahmawati Zaimah (Mantiqu Tayr: Journal of Arabic Language, 2023)
The process of learning a foreign language in early childhood greatly influences their psychological development. Because of that, teachers are expected to be able to provide variations in each foreign language learning. Interesting learning methods will make children feel happy and not pressured in the process of learning a foreign language.The background of this research is the suitability of foreign language learning in early childhood, due to the lack of adjustment between the roles of parents and teachers in the foreign language learning process.Therefore, researchers are interested in conducting research related to the relevance of foreign language learning. This study aims to determine the suitability of foreign language learning for early childhood.The type of research used is literature study, data collection techniques by examining books, journals, and articles related to the research topic.The result of this literature study is that learning foreign languages   for early childhood is very relevant by using a variety of learning methods.In addition to learning methods, the role of teachers and parents also influences the process of learning foreign languages   for children. Creating a happy learning atmosphere can also accelerate children's comprehension in learning foreign languages.In psychology, the human brain has been genetically prepared for language, its connection with the existence of foreign language learning for early childhood is to improve human language power as early as possible.